Durability of pretensioned concrete girders in coastal climate bridges: Basis for better maintenance and future design. (30th July 2019) - Osmolska, Magdalena J.; Kanstad, Terje; Hendriks, Max A. N.; Hornbostel, Karla; Markeset, Gro
Abstract: This study was based on findings from the Norwegian Public Roads Administration's Bridge Management System and field investigations on corrosion damage in pretensioned Norwegian standard I‐beam (NIB) girders in 227 coastal climate bridges. The main durability design parameters are summarized and related to regulations over the last 80 years. Environmental exposure is discussed in the light of the global, local, and micro climate. We found that 51% of the bridges have girder corrosion damage. The percentage is highest for bridges built when the cover thickness required was lowest. Cover thickness below that required (resulting from production faults) caused 74% of corrosion damage. Most of the severe chloride‐induced corrosion damage in bridges was found in the inner NIB girders, particularly in the support‐zones and their vicinity. This can be due to interaction between geometry and exposure. Corrosion of reinforcement in support‐zones can impact structural behavior, particularly NIB girder shear performance.